Matczyne czynniki zagrożenia a wewnątrzmaciczne opóźnienie rozwoju - Cieślik, Krystyna (Polskie Towarzystwo Antropologiczne, 1996)
This paper is a part of a research which aims to compare the level of foetuses growth according to the influence of maternal factors of threat.
Maternal factors of threat and an intrauterine growth retardation